Phytochemical, Nutritional And Antioxidant Activity Evaluation Of Seeds Of Jackfruit (Artocarpous Heterolphyllus Lam.) - DEEPIKA GUPTA; SONIA MANN; AVIJIT SOOD; RAJINDER K. GUPTA (International Journal of Pharma and Bio Sciences, 2011)
In the present work, we have investigated nutritional, phytochemical content and antioxidant activity of seeds of the jackfruit (Artocarpus heterophyllus Lam.), one of the most ancient fruit indigenous to Western Ghats of India. The antioxidant properties were evaluated using free radical scavenging, metal chelating, ferric reducing antioxidant power and reducing power assays. Secondary metabolites including alkaloids, saponins, flavanoids and phenolics content were determined in the jackfruit seeds. Nutritional properties including moisture, fats, carbohydrates, proteins, ash content and metal content in the seeds were also estimated. Polyphenolic content and antioxidant properties of dichloromethane: methanol (1:1) extract of jackfruit seeds was found to be high and well correlated. Results indicated jackfruit seeds to be a good source of nutritional and antioxidant components and hold their potential for value addition and nutraceutical development.